MINIMISE AD (?/*IN-)FINITUM? IN DEFENSE OF WEAKLY CARTOGRAPHIC COMPUTATIONAL MODELS - Cegłowski, Piotr (Versita Ltd., de Gruyter, 2008)
This paper provides a critical overview of the strongly derivational and non-cartographic approaches to syntax based solely on the relation between a newly selected lexical item (LI) and the so-called derivational space (the existing syntactic object) treated as the pivot of the syntactic derivation. Specifically, it is argued that, given the asymmetry requirement requisite for lineariza- tion, as stated in Kayne’s (1994) Linear Correspondence Axiom (LCA) and Chomsky’s (1994) Bare Phrase Structure (BPS), the abovementioned procedure is unattainable in certain strongly derivational syntactic configurations. The latter sections of the paper, while still arguing against the excessively minimized derivational space, focus on the non-cartographic Escape system pro- posed by Zwart (2007). It is shown that the data (comprising mostly the so-called “look-ahead”- based cases) that prove problematic for Escape can be captured within a moderately (i.e. weakly) cartographic view of the left periphery in accord with Thráinsson’s (1996) Limited Diversity Hypothesis.
Keywords: left periphery; (non-)cartohraphic syntax; look-ahead; linearization; assymetry